Ambientes favoráveis à produção dos fonemas fricativos /z/, / ʃ / ʒ / no tratamento do desvio fonológico - Wiethan, Fernanda Marafiga (2011)
This study aimed at examining and comparing the effects of phonological therapy in two groups of children with phonological disorder, one using words with favorable phonological environments and another one with unfavorable and neutral contexts, in the acquisition of the fricative consonants /z/, // and //. The sample consisted of six subjects with phonological disorder, aged between 4:7 and 7:8, who were authorized by their parents to participate in the research by signing the Term of Free Informed Consent. The subjects should: present alterations only in the phonological level of language; not have acquired at least two of the phonemes /z/, // and //; be aged between 4:0 and 8:0; be a member of a monolingual family speaker of Brazilian Portuguese; not have undergone speech therapy before. The following evaluations were made: interview with the parents, phonological evaluation, evaluation of the stomatognathic system, of language, of vocabulary, of phonological awareness skills and of auditory processing, in addition to the complementary exams: audiological and otorrinolaringological ones. The subjects were matched according to the severity of the phonological disorder, sex, age and aspects of the phonological system in relation to the altered phonemes. Half the children were treated with words in which the phonemes /z/, // and // were in favorable environments and the other half with unfavorable and neutral environments. The Modified Cycles Model was adopted and adapted to the research needs. There were eight sessions for each child and, after them, a new speech evaluation was performed, in order to check the changes in the phonological systems and the types of generalization obtained. For the analysis of the variables acquired phonemes in the phonological system, percentage of correct productions of the phonemes /z/, // and // and Percentage of Consonants Correct-Revised, the software SAS (Statistical Analysis System), version 8.02, was used with the Wilcoxon Test significance level of 5%. The analyses of the generalizations and of the routes of phonological acquisition were qualitative, by comparing the initial and the final evaluations. The results of the statistical analyses indicated that the therapeutic improvements were statistically significant (p< 0,05) for all the subjects in most variables, but in the comparisons between the groups favorable and unfavorable and neutral there was no statistically significant difference (p> 0,05). All types of generalization were observed and there was a certain advantage of the children who were treated with favorable environments in the generalizations to lexical items that were not used in the treatment , to another position in the word and inside a sound class , but the generalization to other sound classes was similar among the subjects. As for the route of phonological acquisition, there was a small advantage in the therapeutic improvements of two subjects treated with favorable environments in relation to their matches. However, a child treated with unfavorable and neutral environments obtained better results than her match. Therefore, it was possible to conclude that the favorable environments to the production of the fricatives /z/, // and // did not determine the therapeutic success, but positively influenced the occurrence of generalizations in this study.